Copper-, ligand- and solvent-free synthesis of ynones by coupling acid chlorides with terminal alkynes - Palimkar, Sanjay S.; Kumar, P. Harish; Jogdand, Nivrutti R.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Tetrahedron Letters, 2006)
A general and efficient copper-, ligand- and solvent-free synthesis of ynones by coupling of a wide range of acid chlorides with terminal alkynes catalyzed by palladium(II) acetate at room temperature is reported. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ligandless; neat; ynones

Ligand-, copper-, and amine-free one-pot synthesis of 2-substituted indoles via Sonogashira coupling 5-endo-dig cyclization - Palimkar, Sanjay S.; Kumar, P. Harish; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Tetrahedron, 2006)
Results of the optimized conditions for the one-pot synthesis of 2-substituted indoles via palladium acetate catalyzed tandem Sonogashira coupling 5-endo-dig cyclization at room temperature under ultrasonic irradiation and standard stirred conditions are described. Electron-donating and electron-withdrawing groups present in both Coupling partners were well tolerated under these mild conditions. A copper-, ligand- and amine-free condition is an important feature of this protocol. Significant enhancement of reaction rates was observed for the reactions employing ultrasonic irradiation. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 5-endo-dig cyclization; Indole; synthesis; Ultrasound

Novel one-pot three-component synthesis of 2,4-disubstituted-3H-benzo[b][1,4]diazepines in water - Palimkar, Sanjay S.; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Green Chemistry, 2007)
A novel green and efficient one-pot three-component synthesis of 2,4-disubstituted-3H-benzo[b][1,4]diazepines in excellent isolated yields has been reported. The methodology initially involves the formation of ynones via coupling of a wide range of acid chlorides with terminal alkynes catalysed by Pd(OAc)(2) under copper-, ligand- and solvent-free conditions in just 10 min at rt followed by the Michael addition and cyclocondensation of o-phenylenediamines added in situ using water as a solvent at reflux temprature. In addition, the structure of the benzodiazepine was confirmed to be the diimino molecule and not the enamine by X-ray crystallographic analysis of the benzodiazepine 4b. The methodology is suitable for the operation in combi-chem mode to generate libraries of a diverse array of benzodiazepines. The methodology has been successful in achieving the twin green chemistry objectives of a solvent and ligand free operation and the use of water as a non-hazardous, inexpensive and readily available solvent in the sequential reaction steps performed in situ, thus combining the features of both economic and environmental advantages.

Synthesis of an indole containing KDR kinase inhibitor by tandem Sonogashira coupling-5-endo-dig-cyclization as a key step - Palimkar, Sanjay S.; More, Vijaykumar S.; Kumar, P. Harish; Srinivasan, Kumar V. (Tetrahedron, 2007)
An efficient synthesis of the potent KDR kinase inhibitor 3-[5-[[4-(methylsulfonyl)-1-piperazinyl]methyl]-1H-indol-2-yl]quin oline-2-(1H)-one using a Sonogashira coupling-5-eiido-dig-cyclization strategy is described. (c) 2007 Elsevier Ltd. All rights reserved.

Simple and efficient one-pot, three-component, solvent-free synthesis of beta-enaminones via sonogashira coupling-Michael addition sequences - Palimkar, Sanjay S.; More, Vijaykumar S.; Srinivasan, Kumar V. (Synthetic Communications, 2008)
A simple, efficient, and environmentally friendly one-pot, three-component synthesis of beta-enaminones via Sonogashira coupling-Michael addition sequences under solvent-free conditions has been reported. Also the synthesis of beta-enaminones has been achieved in high yields by the direct reaction of amines with ynones under solvent-free conditions.
Keywords: Alkynes; beta-enaminones; coupling; Michael additions; solvent free; ynones

Ultrasound promoted copper-, ligand- and amine-free synthesis of benzo[b]furans/nitro benzo[b]furans via Sonogashira coupling-5-endo-dig-cyclization - Palimkar, Sanjay S.; More, Vijaykumar S.; Srinivasan, Kumar V. (Ultrasonics Sonochemistry, 2008)
This method describes the results of the optimized conditions for the one-pot synthesis of benzo[b]furans/nitro benzo[b]furans via Sonogashira coupling-5-endo-dig-cyclization under ultrasonic irradiation at ambient temperature in the absence of copper, ligand and amine. The protocol tolerates wide range of functional groups present in both the coupling components, especially base labile nitro group was not affected under these mild conditions giving excellent yields of the nitro benzo[b]furans. The formation of Pd(0) nanoparticles as the active species has been shown by TEM analysis and the unique role of ultrasound in promoting the total sonochemical protocol has been substantiated by way of control experiments. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: 1-alkynes; benzo[b]furans; Sonogashira coupling-5-endo-dig-cyclization